Impact of increasing the availability of healthier vs. less-healthy food on food selection: a randomised laboratory experiment - Rachel Pechey; Olivia Sexton; Saphsa Codling; Theresa M. Marteau (BMC, 2021)
Abstract Background Environmental cues shape behaviour, but few studies compare the impact of targeting healthier vs. less-healthy cues. One online study suggested greater impact on selection from increasing the number of less-healthy (vs. healthier) snacks. The current study aimed to: (1) extend the previous study by using physically-present snacks for immediate consumption; (2) explore responsiveness by socio-economic position; (3) investigate possible mediators (response inhibition, food appeal) of any socio-economic differences in selection. Methods In a between-subjects laboratory experiment UK adults (n = 417) were randomised according to their ID number (without blinding) to one of three ranges of options: Two healthier, two less-healthy ["Equal"] (n = 136); Six healthier, two less-healthy ["Increased Healthier"] (n = 143); Two healthier, six less-healthy ["Increased Less-Healthy"] (n = 138). Participants completed measures of response inhibition and food appeal, and selected a snack for immediate consumption from their allocated range. The primary outcome was selection of a healthier (over less-healthy) snack. Results The odds of selecting a less-healthy snack were 2.9 times higher (95%CIs:1.7,5.1) in the Increased Less-Healthy condition compared to the Equal condition. The odds of selecting a healthier snack were 2.5 times higher (95%CIs:1.5,4.1) in the Increased Healthier (vs. Equal) condition. There was no significant difference in the size of these effects (− 0.2; 95%CIs:-1.1,0.7). Findings were inconclusive with regard to interactions by education, but the direction of effects was consistent with potentially larger impact of the Increased Healthier condition on selection for higher-educated participants, and potentially larger impact of the Increased Less-Healthy condition for less-educated participants. Conclusions A greater impact from increasing the number of less-healthy (over healthier) foods was not replicated when selecting snacks for immediate consumption: both increased selections of the targeted foods with no evidence of a difference in effectiveness. The observed pattern of results suggested possible differential impact by education, albeit not statistically significant. If replicated in larger studies, this could suggest that removing less-healthy options has the potential to reduce health inequalities due to unhealthier diets. Conversely, adding healthier options could have the potential to increase these inequalities. Trial registration ISRCTN: ISRCTN34626166 ; 11/06/2018; Retrospectively registered.